2017
DOI: 10.7341/20171346
|View full text |Cite
|
Sign up to set email alerts
|

Developing Entrepreneurial Skills. An Educational and Intercultural Perspective

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
1
24
0
4
Order By: Relevance
“…Entrepreneurship skills include market awareness, creativity, flexibility [15]. Entrepreneurial skills include performance orientation, creativity, taking initiative, risk taking, perseverance, leadership, communication, problem solving, collaboration/teamwork [16]. Children's entrepreneurship skills are the ability to start something new, discovering opportunities, responsibility, trust, and creativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Entrepreneurship skills include market awareness, creativity, flexibility [15]. Entrepreneurial skills include performance orientation, creativity, taking initiative, risk taking, perseverance, leadership, communication, problem solving, collaboration/teamwork [16]. Children's entrepreneurship skills are the ability to start something new, discovering opportunities, responsibility, trust, and creativity.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While entrepreneurship support programmes vary greatly in duration, structure and content (Garavan and O'Cinneide 1994), there are three main areas of focus: technical skills, business management skills and personal entrepreneurial skills (Hisrich and Peters, 1998). Leon (2017) provides an extensive review of literature relating to the nature of skills identified by researchers as being focused on in enterprise education programmes. These core skills are summarized in Table 1 and mapped onto those described by Hisrich and Peters. Many research and policy initiatives focus on the role of higher education in fostering entrepreneurship and developing entrepreneurial competence (Arthur et al, 2012;Rae and Wang, 2015), and pressures on higher education to become more entrepreneurial have meant that business and management disciplines have seen a large growth in research exploring the teaching of entrepreneurship as a subject (Carey and Matlay 2010).…”
Section: Enterprise Educationmentioning
confidence: 99%
“…Nauwelaers and Wintjes (2003) identify the subsidy for hiring innovation managers in SMEs and the innovation management training and advice among the policy innovations at a firm level. Tödtling and Trippl (2005) point out the need for management schools, which can raise the education/skill level of a region (Leon, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%